Association between oxidative balance score and gallstone in US adults: a cross-sectional study - Chen, Xiaoya; Huo, Xiongwei; Ye, Changchun; Xu, Zhengshui; Chen, Zilu; Liu, Shiyuan (Frontiers in Aging, 2025)
IntroductionThe Oxidative Balance Score (OBS) serves as a means to evaluate the systemic oxidative stress status, where the higher OBS score indicates a greater exposure to antioxidants. Few studies have delved into the connection between the systemic oxidative stress status and gallstone.MethodsA total of 4,376 from the NHANES participants were included in this cross-sectional analysis using 2017–2020 survey cycles. Gallstone was diagnosed by the Patient Health Questionnaire. OBS was scored by 16 dietary factors and 4 lifestyle factors. Logistic regression, subgroup analysis and restricted cubic splines (RCS) were used to assess the association between OBS and gallstone.ResultsIn a sample comprising 4,376 individuals, logistic regression illuminated a negative association between OBS and gallstone [OR = 0.96 (0.94, 0.98), p < 0.001]. Compared to the lowest quartile of OBS, the fully adjusted ORs for the highest quartile of total OBS and gallstone were 0.65 (0.45, 0.95), p=0.025. Robust associations were also discerned between gallstone and both dietary and lifestyle OBS. The results of the subgroup analysis showed significant differences in the association between lifestyle OBS and gallstone with respect to age and marital status. RCS analysis indicated a significant linear relationship between OBS and gallstone.DiscussionOur study exhibited a reverse relationship between OBS and the prevalence of gallstone among American adults, which provided a theoretical foundation for designing personalized dietary regimens and lifestyle modifications to mitigate gallstone formation.